O abuso do direito - Marcacini, Daniela Tavares Rosa (2006)
This dissertation is the result of the interest in investigating the Rights Abuse conception; polemic subject, studied by several philosophic and ideologic currents which seek, with tireless devotion, the best practice in the juridical field. By means of these facts, and in order to deepen the investigation of the chosen topic, we selected the non structured research methodology of exploring character which allows the researcher obtain a better context comprehension in which is inserted the research subject. As we shall observe, through all the exposed, there is no way for us not to conclude that Rights Abuse is originated by human being s individualism - in its most selfish aspect - once its roots begin from the proper human existence. It is also not exaggerated to affirm that on the day when Rights Abuse cease to be the object of juridical controversies, humanity will have reached such a high evolutive level that the proper right will become the synonym of just, in the widest meaning of the word; justice will be the consequence of social relationship, not needing to be imposed to man by means of laws and convival rules. Therefore, taking in consideration that the sicussion of such a fascinating question will never be exhausted, we effect this investigation as a manner to specify that the Rights Abuse will always continue to be of utmost importance when related to society rights